Early and differential autoimmune diseases diagnosis by interrogating specific autoantibody signatures with multiplexed electrochemical bioplatforms - Beatriz Arévalo; Verónica Serafín; María Garranzo-Asensio; Rodrigo Barderas; Paloma Yáñez-Sedeño; Susana Campuzano; José M. Pingarrón (Biosensors and Bioelectronics: X, 2023)
This work reports the first bioplatform to assist in the early and reliable diagnosis of autoimmune diseases by quadruple determination of autoantibodies (Abs) produced against extractable nuclear antigens (ENAs): La/SSB-Abs, Ro/SSA-Abs, U1snRNP70-Abs and smRNP-Abs. The bioplatform involves indirect immunoassays on the surface of magnetic microcarriers (independent batches for each of the target autoantibodies) and amperometric transduction using the H2O2/hydroquinone (HQ) system on a disposable multiple electrode platform. The magnetic microcarriers were modified with the corresponding antigens using His-tag and carbodiimide/succinimide chemistries and employed for the selective capture of the corresponding autoantibodies. Thereafter, they were enzymatically labelled with a secondary antibody conjugated with horseradish peroxidase (HRP) and magnetically captured on each of the working surfaces of the quadruple platform. The evaluation of the analytical and operational characteristics of the bioplatform for the amperometric determination of standards, performed under optimized experimental conditions, confirmed the bioplatform competitiveness in terms of sensitivity and point-of-care application compared to commercially available ELISA methodologies for the single determination of target Abs. The developed bioplatform was applied to the analysis of serum samples from healthy individuals and from patients with two prevalent autoimmune diseases (systemic lupus erythematosus, SLE, and Sjögren's syndrome, SS). The obtained results proved the potential of the bioplatform for the differential diagnosis of these two autoimmune diseases through the accurate, simple, and rapid multidetermination of the four target Abs.